Early Obesity Prevention: A Randomized Trial of a Practice-Based Intervention in 0–24-Month Infants - Natalia Schroeder; Berenice Rushovich; Edward Bartlett; Sangita Sharma; Joel Gittelsohn; Benjamin Caballero (Journal of Obesity)
Objective. A pediatric office-based intervention was implemented following a randomized, controlled design, aimed at improving child feeding practices and growth patterns and ultimately reducing risk for overweight and obesity later in life. Methods. Four clinics (232 infants) were randomized to control or intervention (I), the latter delivered by health care provider at each of 7–9 well-baby visits over 2 years, using a previously developed program (Growing Leaps and Bounds) that included verbal, visual, and text advice and information for parents. Results. The I group offered significantly less soda p=0.006, sweetened tea p=0.01, punch p=0.02 and/or cow’s milk p=0.001 to infants and delayed the introduction of drink/food other than breast milk p<0.05. Parents in the I group had a higher perceived parental monitoring p=0.05 and restriction p=0.01 on infant feeding. While the I group exhibited at baseline more adverse socioeconomic indicators than the control group, growth trajectory or body size indices did not significantly differ between groups. Conclusions. Education provided by health care providers in addition to follow-up monthly phone calls may help modify parental behaviors related to child feeding and increase parental sense of responsibility toward child eating behaviors.